2019
DOI: 10.1155/2019/6316231
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis and Inhibitory Evaluation of Terminalia catappa Leaf Extracts on Major Enzymes Linked to Diabetes

Abstract: Terminalia catappa leaves are used in managing both diabetes mellitus and its complications in Southwest Nigeria. However, its inhibitory activity on enzymes implicated in diabetes is not very clear. This study investigated the in vitro inhibitory properties and mode of inhibition of T. catappa leaf extracts on enzymes associated with diabetes. The study also identified some bioactive compounds as well as their molecular interaction in the binding pocket of these enzymes. Standard enzyme inhibition and kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Higher β-carotene and lycopene content in NLE is as a result of their classification and structure making them more soluble in ethanol than water [22,23]. Previous studies have reported a higher phytochemical content in their ethanolic extracts than their aqueous thus corroborating the findings in this study [15,24]. Antioxidants scavenge free radicals which are products of metabolism.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Higher β-carotene and lycopene content in NLE is as a result of their classification and structure making them more soluble in ethanol than water [22,23]. Previous studies have reported a higher phytochemical content in their ethanolic extracts than their aqueous thus corroborating the findings in this study [15,24]. Antioxidants scavenge free radicals which are products of metabolism.…”
Section: Discussionsupporting
confidence: 88%
“…The anti-inflammatory activity of this class of phytochemical has been well reported such as the erythrocyte membrane stabilising effect, cation-binding activity of tannins and wound healing properties of lycopene and β-carotene [36][37][38]. Boucherle et al [39] reported the presence of tannins in the leaf extract of N. latifolia buttressing findings 9 Oxidative Medicine and Cellular Longevity usually witnessed with synthetic inhibitors such as acarbose and voglibose [15,42]. This study revealed the promising inhibitory α-amylase and α-glucosidase potential of N. latifolia leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations